TCAD evaluation of single-event burnout hardening design for SiC Schottky diodes. (December 2022) - Chen, Jia-Hao; Wang, Ying; Guo, Hao-min; Fei, Xin-Xing; Yu, Cheng-hao; Bao, Meng-Tian
Abstract: In this paper, a single-event burnout (SEB) hardening technique for Schottky diodes at a linear energy transfer (LET) value of 0.5 pC/μm (75.5 MeV/mg/cm 2 ) is presented and investigated by 2-D numerical simulations. The simulation results show that, when compared with the conventional junction barrier Schottky (JBS) diode with multiple buffer layers, the proposed structure can significantly reduce the electric field at the metal/SiC interface with the help of the trench, thereby reducing the interface temperature. Moreover, the maximum global temperature of the proposed structure is also reduced. The maximum global temperature of the proposed structure is 1989 K and the temperature at the Schottky contact interface is 439 K for the bias voltage of 1000 V and LET value of 0.5 pC/μm (75.5 MeV/mg/cm 2 ) which shows that the new structure has better SEB performance. In addition, the hardening method proposed in this paper can be applied at different breakdown voltages by adjusting the structural parameters of the device. Highlights: The SEB performance of SiC Schottky diode with the trench is investigated. The SEB performance of the proposed SiC Schottky diode is significantly improved. The improvement of SEB performance is mainly due to the introduction of the trench.